Clinical and microbiological characteristics of bacteremia caused by Streptococcus viridans in children with hematologic malignancies - M. V. Panina; G. A. Klyasova; G. A. Novichkova; N. V. Myakova; D. V. Litvinov; D. D. Baydildina; M. A. Maschan; A. A. Maschan (Онкогематология, 2015)
Bacteremia caused by Streptococcus viridans may be fulminant in neutropenic patients. The clinical signs of streptococcal bacteremiain neutropenic patients are obvious, but non-specific, and are characterized by fever, pulmonary symptoms (pneumonia, respiratory distress syndrome) in 20–25 % of cases, hemodynamic instability (about 30 % of cases), rash and followed desquamation, in rare cases – neurological disorders (encephalopathy). Perhaps the main difference from other bacteremia in immunocompromised patients is approximately 10 times higher risk of rapid (during the first two days) development of acute lung injury with hypoxemia often requiring oxygen subsidies and respiratory support. Frequency, clinical characteristics and outcomes of streptococcal bacteremia, as well as the spectrum of antibiotics sensitivity was retrospective analyzed in this study. From 2003 to 2009 in children with various oncological and hematological diseases and febrile neutropenia 265 microorganisms were isolated from blood cultures, including Gram-positive in 113 (42 %) patients. Strains of Streptococcus viridans, isolated at least once from blood (central venous catheter and / or peripheral veins), are included in analysis. Streptococcus viridans were isolated from the blood of 20 patients, accounting for 7.5 % of the total number of bacteremia and 17.7 % of gram-ositive bacteremia. Patients with acute myeloid leukemia (AML) accounted for 45 % of all patients with streptococcal bacteremia, but the incidence of streptococcal bacteremia in AML patients was 8.7 % and did not differ from patients with other diagnoses. 11 (55 %) from 20 patients have mucositis at diagnosis of bacteremia, in 14 patients (70 %) prior chemotherapy included high dose of cytosine arabinoside. All patients with streptococcal bacteremia have severe neutropenia (median 70 cells / mkl) and characterized by fever (100 %), septic shock (8 patients, 40 %) and RDS (7 patients, 35 %) required high doses of steroids (7 patients; 100 %) and ALV (2 patients; 10 %). All patients survived. In 13 (65 %) patients primary empirical therapy contained antibiotics effective against Streptococcus viridans. All strains were susceptible to vancomycin, linezolid and levofloxacin; 90 % and 95 % of strains – to ceftriaxone and cefepime, respectively; 80 % – to penicillin; 50 % – to oxacillin and 35 % – to trimethoprim / sulfomethoxazol.